Approaches for supporting adolescents’ reading motivation: existing research and future priorities - Webber, Charlotte; Wilkinson, Katherine; Duncan, Lynne; McGeown, Sarah (Frontiers in Education, 2023)
Research has consistently demonstrated declines in reading motivation and engagement from childhood to adolescence, with current levels of reading enjoyment and engagement among adolescents at an all-time low. This has led to increased interest in approaches for supporting adolescents’ reading motivation. To date, efforts to support adolescent reading motivation have utilized a variety of approaches, yet there is currently no review which synthesizes existing research in this area and provides recommendations for future research and practice. Drawing upon both narrative and scoping review principles, this review synthesizes 38 peer-reviewed articles and research reports which have evaluated approaches for improving adolescents’ (12-16 years old) reading motivation. The article outlines the breadth and scope of approaches which have been used previously, categorized into five types: (1) reading and literacy skills programs; (2) whole-school reading culture; (3) book clubs; (4) technology-supported interventions; and (5) performance and theater. The review also identifies gaps and issues relating to the current body of research and proposes priorities for future work in this area. Together, the findings and recommendations address calls to dedicate renewed and sustained attention to supporting adolescents’ reading motivation and engagement and provide a point of reference for researchers and education practitioners seeking to select, develop, and implement strategies for supporting adolescents’ reading motivation in the future.